Pengaruh Kualitas Pelayanan Berbasis CHSE Terhadap Loyalitas Wisatawan Dimediasi Kepuasan Wisatawan (Studi Wisatawan Luar Daerah di Kawasan Borobudur) - Novitaningtyas, Ivo; Lionora, Clarisa Alfa; Achsa, Andhatu; Hartono, Budi; Nurhidayah, Siti; Agustin, Hesti (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research examines the impact of implementing the CHSE certification policy in the tourism sector especially the accommodation or hospitality business on tourist behavior based on satisfaction and loyalty. This study uses a quantitative approach. This research uses primary data obtained from 73 tourists selected based on the purposive sampling method. The sample criteria are tourists who have stayed at a hotel or homestay around Borobudur Temple more than once and come from outside the province of Central Java. The data collection method uses questionnaires distributed online and offline. The data analysis method uses PLS-SEM. The results show that tourist satisfaction mediates the influence of CHSE-based service quality on tourist loyalty. The results provide managerial implications for accommodation business managers to become CHSE-certified to satisfy overnight tourists and increase tourist loyalty.